Green Islam Education: Model Pembelajaran Ekopedagogi Berbasis Fikih Lingkungan di Sekolah Islam Urban - Zaimina, Ach. Barocky; Munib, Bahrul (MANAGIERE: Journal of Islamic Educational Management, 2025)
This article explores and develops an ecopedagogical learning model grounded in Islamic environmental fiqh within the context of urban Islamic schools. The findings reveal that integrating core Islamic ecological principles such as khalifah (human stewardship), maslahah (public benefit), hima (environmental protection zones), and the prohibition of ifsad (destruction) enriches contemporary ecopedagogical values with strong spiritual and normative foundations. The model is contextualized to address the unique challenges of urban Islamic schools, including limited green spaces, air pollution, and consumerist culture. Implementation shows that urban contexts can become critical ecological learning spaces through green practices such as energy conservation, waste management, and school-based environmental advocacy. Moreover, this model holds promise as an alternative curriculum framework for Islamic schools aiming to implement systematic environmental education. By integrating thematic, interdisciplinary, and action-oriented approaches, the model emphasizes the development of students’ ecological character rooted in Islamic values and real-life engagement beyond mere cognitive understanding.